An Exploration of The Socio-Economic State of Household Sanitation Project Beneficiaries in George Compound. (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: The study explored the perceived solutions to the sanitation challenges in George Compound in Lusaka, Zambia. The study objective was to assess the socio-economic situation of the beneficiaries of Household Sanitation Project in George Compound. The researcher adopted the social constructivist ontology, knowledge was co-constructed with participants through an interpretive phenomenological approach, and reflexive thematic analysis. The sample was selected purposively and determined using data saturation, ensuring rich, contextual insights from relevant stakeholders. The study revealed that poor sanitation affects men and women differently and it was further observed that women are more affected due to their biological nature, which limit their ability to use public spaces for relief, unlike men who can use open areas. The construction of toilets under the project helped address gender-specific concerns related to sanitation. Moreover, most study participants noted that in the past, cultural norms discriminated against women and favoured men. Similarly, the researcher disclosed that most study participants revealed that toilets constructed by LWSC significantly reduced the disease burden for both men and women. Furthermore, the study revealed that the company offered flexible payment options, making it easier for beneficiaries to access sanitation products. Theoretically, it corroborates systems theory by illustrating the interrelated roles of stakeholders in sustainable sanitation. For policy, the study emphasizes integrated, multi-stakeholder interventions informed by practical experiences. Practically, it highlights the need for community sensitization and engagement to ensure sustainability of sanitation innovations. Knowledge-wise, the study provides contextual evidence specific to George Compound, documenting challenges, innovations, and operational insights that can inform similar peri-urban settings. In conclusion, addressing sanitation challenges in peri-urban Lusaka requires a holistic, systems-oriented approach that integrates infrastructure, regulation, education, cultural socialization, and community participation to ensure equitable, sustainable, and effective on-site sanitation services.